“It's That Route That Makes Us Sick”: Exploring Lay Beliefs About Causes of Post-traumatic Stress Disorder Among Sub-saharan African Asylum Seekers in Germany - Grupp, Freyja; Moro, Marie Rose; Nater, Urs M.; Skandrani, Sara M.; Mewes, Ricarda (Frontiers in Psychiatry, 2018)
Many asylum seekers have been confronted with traumatizing events, leading to high prevalence rates of post-traumatic stress disorder (PTSD). Within the diagnostic context, clinicians should take into account patients’ culturally shaped presentation of symptoms. Therefore, we sought to provide insights into beliefs about causes of PTSD held by Sub-Saharan African asylum seekers living in Germany. To this aim, we used a quantitative and qualitative methodological triangulation strategy based on a vignette describing symptoms of PTSD. In the first part of the study, asylum seekers (n=119), predominantly from Eritrea (n=41), Somalia (n= 36), and Cameroon (n = 25), and a German comparison sample without a migration background (n=120) completed the Revised Illness Perception Questionnaire (IPQ-R). In the second part, asylum seekers reviewed the results within eight focus group discussions (n=26), sampled from groups of the three main countries of origin. Descriptive analyses of the first part demonstrated that asylum seekers predominantly attributed PTSD symptoms to psychological and religious causes, and rather disagreed with supernatural causes. In comparison to the German sample without a migration background, asylum seekers attributed symptoms less strongly to terrible experiences, but more strongly to religious and supernatural causes. Within the focus group discussions, six attribution categories of participants’ causal beliefs were identified: (a) traumatic life experiences, (b) psychological causes, (c) social causes, (d) post-migration stressors, (e) religious causes, and (f) supernatural causes. Our findings suggest that the current Western understanding of PTSD is as relevant to migrants as to non-migrants in terms of psychological causation, but might differ regarding the religious and supernatural realm. While awareness of culture-specific belief systems of asylum seekers from Sub-Saharan Africa regarding PTSD is important, our findings do underline, at the same time, that cultural differences should not be overstated.